2020
DOI: 10.1016/j.eclinm.2020.100604
|View full text |Cite
|
Sign up to set email alerts
|

Impaired spermatogenesis in COVID-19 patients

Abstract: Background The current study aimed to determine the impact of SARS-CoV-2 infection on male fertility. Methods This is a single-center, hospital-based observational study that included autopsied testicular and epididymal specimens of deceased COVID-19 male patients ( n =6) and recruited recovering COVID-19 inpatients ( n =23) with an equal number of age-matched controls, respectively. We performed histopathological ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
320
2
24

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(354 citation statements)
references
References 33 publications
(52 reference statements)
8
320
2
24
Order By: Relevance
“…Infection may also take place after touching an infected surface followed by touching the mouth, nose, or eyes ( Stadnytskyi et al, 2020 ). Moreover, clinical research has reported that other routes of contagion may occur, such as via contact with the blood ( Yu et al, 2020 ), feces ( Cheung et al, 2020 ), or semen ( Li et al, 2020a , Li et al, 2020b , Li et al, 2020c ) of an infected person.…”
Section: Potential Of Sexual Transmission and Impacts On Sexual Behavmentioning
confidence: 99%
See 4 more Smart Citations
“…Infection may also take place after touching an infected surface followed by touching the mouth, nose, or eyes ( Stadnytskyi et al, 2020 ). Moreover, clinical research has reported that other routes of contagion may occur, such as via contact with the blood ( Yu et al, 2020 ), feces ( Cheung et al, 2020 ), or semen ( Li et al, 2020a , Li et al, 2020b , Li et al, 2020c ) of an infected person.…”
Section: Potential Of Sexual Transmission and Impacts On Sexual Behavmentioning
confidence: 99%
“…In males, COVID-19 virus can affect male fertility through increasing the body temperature and subsequently the incidence of fever ( Fan et al, 2020 ). Around 80% of COVID-19 patients were reported to exhibit sustained increases in body temperature ( Li et al, 2020a , Li et al, 2020b , Li et al, 2020c ). It has also been suggested that fever and the increase of patients’ testicular temperature can damage spermatogenesis and thus male fertility ( Younis et al, 2020 ).…”
Section: Impacts Of Covid-19 On Gonad Functionsmentioning
confidence: 99%
See 3 more Smart Citations